Distributed Ledger Enabled Control of Tyre Induced Particulate Matter in Smart Cities - Katsikouli, Panagiota; Ferraro, Pietro; Richardson, Hugo; Cheng, Hanson; Anderson, Siobhan; Mallya, Deepak; Timoney, David; Masen, Marc; Shorten, Robert (Frontiers in Sustainable Cities, 2020)
The link between transport related emissions and human health is a major issue for municipalities worldwide and one of the main challenges to address in the context of Smart Cities. Specifically, Particulate Matter (PM) emissions from exhaust and non-exhaust sources are one of the main worrying contributors to air-pollution. In this paper, we challenge the notion that a ban on internal combustion engine vehicles will result in clean and safe air in our cities, since emissions from tyres and other non-exhaust sources are expected to increase in the near future. We support this claim through simple calculations, based on publicly available data from the city of Dublin, and we present a high level solution to this problem, in the form of a control mechanism and ride-sharing scheme to limit the number of vehicles and therefore maintain the amount of transport-related PM to safe levels. Thanks to the use of Distributed Ledger Technology our proposal is entirely distributed, fair and privacy preserving, which makes it ideal for application in the Smart City domain.